The Application of Technology-Enhanced Learning in the Development of Islamic Religious Education in Early Childhood - Sulastri, Sulastri; Ismail, Ismail (Absorbent Mind, 2025)
This qualitative descriptive study explores the use of Technology-Enhanced Learning (TEL) in the development of Islamic Religious Education (PAI) for early childhood at PAUD Diantara Putro Melati Kasihan, Bantul, Yogyakarta. Data were collected through learning observations utilizing educational applications, animated videos, and interactive stories; in-depth interviews with the principal, PAI teachers, and parents; and documentation of technology-based policies and materials. The analysis followed the Miles and Huberman model (data reduction, narrative presentation, triangulation verification) to produce a comprehensive picture. The results showed that digital media—animated stories of the prophets and interactive applications—increased interest, understanding of Islamic values, and social interaction via Google Classroom and Zoom. Regular exposure to technology-based religious content also strengthened positive characters such as politeness and helping each other. However, limited devices, uneven internet access, and the potential for gadget addiction require close collaboration between schools and parents so that the use of technology is balanced and supports future PAI goals. The implementation of TEL has proven effective in developing PAI for early childhood.